Can Nanobubble Ozone Liposomes be a New Agent in the Fight Against Foodborne Infections? - Alkan, Perihan E.; GüneŦ#159, Mesut Ertan; Sabanci, Ahmet æ#156;mit (Recent Patents on Nanotechnology, 2024)
Background: In our study, a nanoparticle liposome molecule with patent application number TR2021004032 was used, and the Minimum Inhibitor Concentration (MIC) was found to be 1562 ppm. According to the ASTM F 1980 standard, it has been determined that the nanoparticle liposome solution kept at 37 days and 55 oC in return for one-year stability preserves its effectiveness. Our study aimed to show that the newly developed solution maintains its effectiveness for a long time.Methods: This study used a nanobubble ozone liposome solution containing 2% ZnCl2. The aging tests were conducted according to the ASTM F 1980 standards. The minimum inhibitory concentration (MIC) level of the nanobubble ozone liposome solution with 2% ZnCl2 was determined as 1.562 ppm for strains of Staphylococcus aureus (ATCC 25923) and Escherichia coli (ATCC 25922) by the CLSI M07 A9 standard test method. The solution's efficiency at a concentration of 2000 ppm and for different time intervals was tested on strains of Salmonella enterica subsp. enterica (ATCC® 14028132;¢) and Listeria monocytogenes (ATCC® 7644132;¢) to assess the time-dependent antibacterial effect of the nanobubble liposome solution with 2% ZnCl2.Results: The results showed the antibacterial activity of the strains of S. enterica subsp. enterica started at the end of the 10th minute, and the solution was effective after 30 minutes. For strains of L. monocytogenes, it was observed that the activity started at the end of the 2nd minute, and the product was effective after the 10th minute. According to the ASTM F 1980 standards, it was found that the nanobubble ozone liposome solution retained its effectiveness in one-year stability tests.Conclusion: As a result, the nanoparticle liposome solution, a new product, does not lose its stability and effectiveness for a long time, contrary to what is known. Although the half-life of gaseous ozone is as short as 20 minutes, the stability in the nanoparticle liposome solution has been determined as at least one year. Since nanoparticle liposome solution is a natural and slow-release product, nanobubble ozone liposome solution with 2% ZnCl2 may be used as a newly developed agent against contaminations in food processing facilities caused by biofilm-forming microorganisms through the disinfection of surfaces that are in direct contact with food products.
Keywords: antibacterial activity